Gender representation and language politeness in speech acts: A pragmatic study - Widyatmike Gede Mulawarman; Yusak Hudiyono; Andri Andri; Hanik Wahyu Ningsi (Masyarakat, Kebudayaan dan Politik, 2021)
Language affects society because linguistic forms treat men and women discriminatively as a reflection of the strong influence of language on the culture or habits of the speaking community. This study aimed to describe the representation of gender in speech and language politeness of senior high school and vocational school students in Samarinda City and Kutai Kertanegara Regency. The method used in this research was descriptive qualitative. The results of this study showed first, for the speech form by female students towards female teachers, they dominantly used the following forms: positive speech, expressive speech, and assertive speech. Second, for the speech form of female students towards male teachers, they preferred the form: expressive speech and assertive speech. Third, for the speech form of male students towards female teachers, they used the following forms: positive speech, commissive speech, and assertive speech. Fourth, the speech form of male students towards male teachers was expressive. Fifth, gender representation in student’s language politeness showed that female students were more likely to comply and male students were more likely to deviate from the principles of linguistic politeness. This study concludes female students followed the principle of language politeness towards female teachers. Male students expressed more deviations towards male teachers.